Airfield and Highway Pavements 2023 : Design, Construction, Condition Evaluation, and Management of Pavements. - Garg, Navneet; Bhasin, Amit; Vandenbossche, Julie Marie (American Society of Civil Engineers, 2023)
This collection contains 40 peer-reviewed papers on the design, construction, evaluation, and management of pavements presented at the International Airfield and Highway Pavements Conference 2023, held in Austin, Texas, June 14-17, 2023.